Korelasi Kadar Kolesterol Total dan Tekanan Darah pada Orang Dewasa di Bangetayu Kota Semarang - Ririh Jatmi Wikandari; Devi Etivia Purlinda; Burhanudin Ichsan (Poltekkes Kemenkes Semarang, 2023)
Non-communicable diseases (NCDs) are the largest contributor to death in the world. The prevalence of NCDs tends to increase. Hypertension is one of the non-communicable diseases with the largest proportion in Semarang. High cholesterol levels will accumulate in the arteries, causing the arteries to stiffen, so the heart tries hard to pump blood through these blood vessels, and can cause blood pressure to rise (hypertension). Some risk factors that can increase blood pressure, such as high salt intake, overweight or obesity, alcohol consumption, lack of physical activity, stress and smoking. Lack of physical activity can increase cholesterol levels in the body which is a risk factor for cardiovascular disease (coroner's heart disease dan stroke). Age affects the occurrence of hypertension. With age the risk of developing hypertension is greater. The purpose of the study was to determine the relationship between cholesterol and blood pressure in adults in Bangetayu, Semarang City. This study uses a cross-sectional approach. Research samples are in the community of Bangetayu Kota Semarang. Research Tools and Materials include lanceolate, alcohol swab, cholesterol strips, digital sphygmomanometers, POCT cholesterol and capillary blood. Research data obtained from the results of checking cholesterol levels and blood pressure. The results of this study were processed using SPSS 20 software with data analysis using Chi Square (α=5%) and presented descriptively about the relationship of cholesterol levels with blood pressure in adults. The results of statistical analysis show a p-value 0.05 which means that there is no significant relationship between variables and vice versa. The results showed that there was no relationship between blood pressure and cholesterol.